Improving the Pedagogic Competence of Lecturers in Religious Universities: Challenges and Solutions - Sukri, Urbanus (Raudhah Publisher, 2025)
This article explores the critical issue of enhancing the pedagogical competence of lecturers at religious higher education institutions. Pedagogical competence is essential for lecturers to effectively deliver knowledge, foster critical thinking, and create an engaging learning environment. However, many lecturers face challenges in adapting to contemporary educational demands, such as integrating technology, applying innovative teaching strategies, and addressing diverse student needs. This study employs a qualitative approach through literature review and library research methods to identify the primary challenges and propose viable solutions. The findings indicate that limited professional development opportunities, insufficient institutional support, and resistance to change are the main obstacles. To overcome these barriers, the article suggests continuous training programs, collaborative learning environments, and institutional policies that encourage pedagogical enhancement. By fostering a culture of continuous learning and innovation, religious higher education institutions can significantly improve the teaching quality of their lecturers. This, in turn, contributes to better student outcomes and aligns educational practices with global standards. The research highlights the importance of ongoing collaboration between lecturers, educational leaders, and policymakers to create sustainable pedagogical improvements. The study concludes that addressing these challenges systematically will not only benefit lecturers but also enrich the overall academic environment at religious higher education institutions.